Allogeneic hematopoietic cell transplantation in a patient with disseminated fusariosis and acute myeloid leukemia - Muñoz, Agustín Matías; Bendek, Georgina; Benso, José Daniel; Ducatenzeiler, Laura; Fernández Otero, Lucas; Giménez, Alberto; Paulin, Pilar; Seehaus, Cristian; Arma, Irene (Revista del Hospital Italiano de Buenos Aires, 2017)
Disseminated fusariosis has become an increasing problem in people with hematopoietic neoplasms, mainly in patients affected by acute leukemias, and even more in those who undergo hematopoietic cell transplantation. There is not an optimal treatment for disseminated fusariosis. The global mortality described in the literature is between 50% and 80%. We introduce a case of a 29 year old patient with diagnosis of acute myeloid leukemia complicated with disseminated fusariosis, who copes with an allogeneic hematopoietic cell transplantation with a successful outcome in the “Hospital Italiano de San Justo” (Argentina)
Keywords: disseminated fusariosis; acute myeloid leukemia; allogeneic hematopoietic cell transplantation